'Don't play if you can't win': does economic inequality undermine political equality?. Issue 3 (25th September 2019) - Schäfer, Armin; Schwander, Hanna
Abstract: In this paper, we investigate whether income inequality negatively affects voter turnout. Despite some progress, the answer to this question is still debated due to methodological disagreements and differences in the selection of countries and time periods. We contribute to this debate by triangulating data and methods. More specifically, we use three kinds of data to resolve the question: first, we use cross-sectional aggregate data of 21 OECD countries in the time period from 1980 to 2014 to study the relationship between inequality and electoral participation. Second, we zoom in on the German case and examine local data from 402 administrative districts between 1998 and 2017. Focusing on within-country variation eliminates differences that are linked to features of the political system. Finally, we combine survey data with macro-data to investigate the impact of inequality on individual voting. This final step also allows us to test whether the effect of income inequality on voter turnout differs across income groups. Taken together, we offer the most comprehensive analysis of the impact of social inequality on political inequality to date. We corroborate accounts that argue that economic inequality exacerbates participatory inequality.